2006
DOI: 10.1177/097215090600700201
|View full text |Cite
|
Sign up to set email alerts
|

FDI, Skilled Labour and the Caribbean's Emerging Competitive Disadvantage

Abstract: This article analyses why the Caribbean economies have not been able to take advantage of their physical proximity to the highly developed economies and the likely role of shortage of skilled labour in this. Our analysis reveals that the twin trends of growing need for FDI and lack of enough highly-skilled workers is giving rise to the emerging competitive disadvantage of the Caribbean countries. We show that in spite of having achieved high levels of human development, including high literacy levels, the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Second, although resource-based view captures important firm resources, researchers could examine the effects on innovation activities based on other enablers such as varied temporal dispositions that are an important source of competitive advantage, especially in the start-up set-up. Adopting a long-term time horizon gives resource insights necessary for innovation and competitiveness, promoting entrepreneurial actions (Bhaumik & Banik, 2006; Bluedorn & Martin, 2008).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Second, although resource-based view captures important firm resources, researchers could examine the effects on innovation activities based on other enablers such as varied temporal dispositions that are an important source of competitive advantage, especially in the start-up set-up. Adopting a long-term time horizon gives resource insights necessary for innovation and competitiveness, promoting entrepreneurial actions (Bhaumik & Banik, 2006; Bluedorn & Martin, 2008).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Kamath (2008) argued that FDI has a significant positive impact on both export and economic growth in India. The development of educational institution, development of knowledge-intensive industries and proper use of information technology are essential factors contributing towards the development of the Caribbean economies (Bhaumik & Banik, 2006). Bhandari, Dhakal, Pradhan and Upadhyaya (2007) examined the impact of foreign aid and FDI on various East European Countries and found that an increase in the stock of domestic capital and inflow of FDI has shown a significant positive impact on economic growth whereas foreign aid has shown an insignificant impact.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Service firms possess certain characteristics that differentiate them from manufacturing firms such as intangibility, inseparability of production and consumption, perishability and heterogeneity (Boddewyn, Halbrich, & Perry, 1986; Knight, 1999). Moreover, literature on international trade and FDI routinely makes a distinction between manufacturing and services sectors (Banik & Bhaumik, 2014; Bhaumik & Banik, 2006). Each service encounter with the customer is unique; therefore, services cannot be standardized and shipped overseas to the same extent as manufactured products.…”
Section: Objectivesmentioning
confidence: 99%